Intersubband transitions in quantum structures - Paiella, Roberto; Sirtori, Carlo; Teissier, Roland; Tredicucci, Alessandro; Kohler, Rudiger; Martini, Rainer; Elsaesser, Thomas; Gmachl, Claire; Malis, Oana; Belyanin, Alexey; Troccoli, Mariano; Capasso, Federico; et al. (McGraw-Hill's AccessEngineering., 2006)
"This volume provides a comprehensive review of the basic physics and applications of optoelectronic devices based on intersubband transitions in semiconductor quantum structures. This book will be useful to scientists and engineers engaged in research and development work on intersubband devices, as well as graduate students interested in the fields of semiconductor quantum structures and optoelectronic devices."--Jacket.